Investigating the Role of English Proficiency in Accounting Students’ Career Readiness in the Global Economy - Suhartina R (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
This study investigates the contribution of English proficiency, learning motivation, and social support to the professionalism and learning strategies of accounting students in the global era. Employing a quantitative descriptive method with a survey design, data were collected from 90 students enrolled in the Accounting Study Programs at LPI College of Economics (STIE LPI) Makassar, YAPI College of Economics (STIE YAPI) Bone, and the Accounting Study Program at the AMKOP School of Economics in South Sulawesi. The research instrument consisted of a structured questionnaire analyzed using descriptive statistical techniques. The results revealed that the majority of students perceived English reading, writing, listening, and speaking skills as essential to their future careers. In particular, 72% highlighted the importance of English reading for accessing international accounting standards, while 68% emphasized writing for professional communication. Grammar mastery was also recognized as a foundational skill by 60% of respondents. Furthermore, 75% agreed that English fluency increases employability, and 67% supported the integration of English into the accounting curriculum. Institutional support was deemed adequate by 62% of participants, though there were noted calls for improvement. These findings indicate that English proficiency, along with learning motivation and social support, is positively associated with students’ academic and professional readiness. Therefore, it is recommended that curriculum development includes English for Specific Purposes (ESP), supported by institutional programs to strengthen language acquisition. Universities are encouraged to provide ongoing English language training, motivation-enhancing activities, and platforms for social engagement to support the holistic development of accounting students in the global professional context.